Penares sp sponge from Menjangan Island-water West Bali National Park: Isolation of Cytotoxic Compounds - Erna Prawita Setyowati; Sudarsono Sudarsono; Retno Murwanti (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Sponges are multicellular animals which have cytotoxic compounds. In this study, isolation and cytotoxic activity of Penares sp sponge from Menjangan island-water West Bali National Park have been carried out. The results showed that chloroform extract and GF V Penares sp fraction were toxic according to Brine Shrimp Lethality Test method (each 85% and 63.3% mortality at 25μg/mL concentration). The isolation result of GF V fraction was obtained a compound (Spot 4) that is active as cytotoxic agent against T47D cells (IC50 of 12.7 ug/mL). Spot 4 is a terpenoid compound which has conjugated double bonds.